1996
DOI: 10.1097/00004694-199607000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Use of Orthofix T-Garche Fixator in Late-Onset Tibia Vara

Abstract: The treatment of late-onset tibia vara has not been well described. High tibial corticotomies and use of the Orthofix T-Garche fixator were performed on 11 children (14 knees) with late-onset tibia vara. The average age at surgery was 12 years, and follow-up was 2 years. Minimum follow-up was until completion of growth. Angular deformities were measured by using the tibiofemoral angle, metaphyseal-diaphyseal angle, and the mechanical axis both preoperatively and on removal of the fixation device. Union was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Price et al demonstrated that monolateral fixation with either acute or gradual correction can effectively correct the tibial varus deformity in the frontal plane 48 . Alignment in the sagittal plane and rotational correction are more difficult to obtain with use of the monolateral fixator 21,50 . A detailed preoperative plan is essential for any surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Price et al demonstrated that monolateral fixation with either acute or gradual correction can effectively correct the tibial varus deformity in the frontal plane 48 . Alignment in the sagittal plane and rotational correction are more difficult to obtain with use of the monolateral fixator 21,50 . A detailed preoperative plan is essential for any surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The values that we obtained for the PPTA in both groups were slightly lower than those previously reported for circular external fixators 2,7,16 but similar to those previously reported for unilateral fixators. 10,21 In our study, all of the cases which recurred occurred in patients with infantile tibia vara, with 64% occurring in limbs that had previously had surgical correction of tibia vara. 2,7Y9,11,14Y22 In particular, the most common complication that occurred was superficial infection treated with oral antibiotics, which has been reported previously in 7% to 100% of patients treated for Blount with external fixation.…”
Section: Discussionmentioning
confidence: 52%
“…1Y6 Gradual correction of Blount disease has been described with both unilateral and circular external fixators. 9 Advantages of unilateral fixators include ease of application, 10,11 fewer pin sites, and less restriction of knee motion. 2,7,8 Disadvantages of circular fixators include a steep surgical learning curve and complexity of postoperative correction required by the patient.…”
mentioning
confidence: 99%
“…It is our belief that the abnormal growth plate cannot respond to the surgery and form a bony bridge. Histopathologic changes have been described in the growth plate and the metaphysis in patients with Blount's disease [8,19]. These changes lead to deformity and growth impairment due to disorientation and disorganization of the columnar pattern of the chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal treatment for patients with late-onset tibia vara is still debated [2,8]. Different types of proximal tibial or distal femoral osteotomy, hemiepiphysiodesis or asymmetric physeal distraction, have been proposed in the literature [1,6,20].…”
Section: Introductionmentioning
confidence: 99%